1987
DOI: 10.1021/bi00398a061
|View full text |Cite
|
Sign up to set email alerts
|

Partial purification and characterization of .beta.-mannosyltransferase from suspension-cultured soybean cells

Abstract: The beta-mannosyltransferase that catalyzes the synthesis of Man-beta-GlcNAc-GlcNAc-PP-dolichol from GDP-mannose and dolichyl-PP-GlcNAc-GlcNAc was solubilized from microsomes of suspension-cultured soybean cells by treatment with 1.5% Triton X-100 and was purified about 700-fold by chromatography on DEAE-cellulose, hydroxylapatite, and a GDP affinity column. The purified enzyme was reasonably stable in the presence of 20% glycerol and 0.5 mM dithiothreitol. The enzyme required either detergent (Triton X-100 or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

1991
1991
1998
1998

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 35 publications
0
1
1
Order By: Relevance
“…The transferase from the pea internodes, unlike the soybean enzyme, did not require divalent cations for its activity nor did EDTA and EGTA alter its activity. The K~ value for the mannan synthesis is different from that reported for the Man-13-GlcNAc-GlcNAc-PP-dolichol formation brought about by the preparation reported by Kaushal and Elbein (1987).…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…The transferase from the pea internodes, unlike the soybean enzyme, did not require divalent cations for its activity nor did EDTA and EGTA alter its activity. The K~ value for the mannan synthesis is different from that reported for the Man-13-GlcNAc-GlcNAc-PP-dolichol formation brought about by the preparation reported by Kaushal and Elbein (1987).…”
Section: Discussioncontrasting
confidence: 83%
“…However, in the present study, no lipid linked mono-or oligosaccharides were found in the incubations during the synthesis. Our enzymic preparations do not have the characteristics of the mannosyl transferase isolated from soybean cells that was shown to be involved in the formation of the mannose oligosaccharides attached to dolichol, and hence to glycoproteins (Kaushal and Elbein 1987). Triton X-100 inhibited the activity of the mannosyl transferase described here whereas this detergent was used to solubilize and activate the enzyme from soybean cells.…”
Section: Discussionmentioning
confidence: 93%